Pendidikan Ekonomi Dan Pengaruhnya Pada Perilaku Konsumtif Siswa Dalam Belanja Ritel Online - Dilan Arya Saputra (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Economic education is a branch of education that focuses on the study of the economy from its understanding to its influence on life. The economics education study program prepares students to become economics teachers in the future. Meanwhile, educational economics is a science that studies how humans and society choose to use money or not to utilize scarce productive resources to produce various types of training and development of knowledge, skills, thinking power, character and so on. Automatically, economic education influences every human behavior, including students' consumptive nature or desire to shop. Technological advances that provide easy access to online shopping make a person's consumptive nature increasingly high